Desenvolvimento de Nested-PCR para identificação do grupo Apicomplexa e de espécies de Plasmodium spp. que causam infecção humana - Souza, Maria Fernanda Bezerra de (2021)
Diseases caused by protozoa of the Apicomplexa group are highly prevalent in Brazil, and often the identification of these organisms is not simple, which makes diagnosis difficult. Within the Apicomplexa group, there is the genus Plasmodium, which comprises the causative agents of malaria, one of the parasitic diseases that causes the greatest number of deaths worldwide. Currently, seven species of the genus Plasmodium are observed infecting humans: Plasmodium vivax, Plasmodium falciparum, Plasmodium malariae, Plasmodium ovale, Plasmodium knowlesi, Plasmodium cynomolgi e Plasmodium simium. The identification of these protozoa is still a challenge, especially when one intends to identify them at the species level. In this context, two new systems were developed through the present work: (1) a Nested-PCR for identification of Apicomplexa based on the 18S rDNA marker, and (2) a Nested-PCR for identification of the main species of Plasmodium that occur in Brazil. The system for identification of Apicomplexa was first validated in silico, and regions 18S rDNA gene that allowed to discriminate the main elements of this group were identified. For in vitro validation samples containing humans, P. falciparum, and Toxoplasma gondii DNA were used and the developed system was compared to marker systems internationally used as reference. The primers used in PCR for detection of Apicomplexa did not amplify human DNA, which allowed greater sensitivity and specificity when compared to the primers used as reference. Once the development of the system for the identification of the Apicomplexa group was completed, the development of a system that would allow discrimination within the genus Plasmodium began. For this purpose, in an initial in silico approach, markers that could discriminate the different species of Plasmodium that cause human malaria were selected, through the GenBank and plasmoDB databases, and the data were processed in programs for alignment and comparison between the sequences such as MAFFT and Geneious. The gene chosen as a molecular marker for Plasmodium was Merozoite Surface Protein 1 (MSP1). The set of primers for the identification of Plasmodium was constructed to produce amplicons of different sizes for each of the six species, enabling the identification of the six species of Plasmodium (P. vivax, P. falciparum, P. malariae, P. ovale, P. knowlesi, and P. cynomolgi) without the need for sequencing. The Nested-PCR for identification of P. vivax and P. falciparum was validated in vitro using detection limit tests, annealing temperature gradient, and specificity test. The specific primers for P. vivax and P. falciparum were validated through verification of amplification, from infected cell culture samples and patients. Nested-PCRs were effective in discriminating between P. vivax and P. falciparum, and we believe that they can be useful tools for the diagnosis of malaria in Brazil. The joint application of the system to the 18S rDNA target can be used as an initial screening aiming at the detection of parasites of the Apicomplexa group, followed by the use of the MSP1 target to determine the Plasmodium species.